Leverage, Capital Intensity, dan Agresivitas Pajak dengan Komisaris Independen sebagai Variabel Pemoderasi - Tanjaya, Ryo Dwantara; Jati, I Ketut (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
The aim of the research is to see how leverage and capital intensity influence tax aggressiveness in companies and to see whether independent commissioners in the relationship between leverage and capital intensity influence corporate tax aggressiveness. The population is companies operating in the basic industrial and chemical manufacturing sector, totaling 78 companies, with a sample of 28 companies determined using a non-probability sampling method with purposive sampling technique used as the sampling technique. The analysis technique uses Moderated Regression Analysis. The results of this research say that Leverage has a positive influence on tax aggressiveness. Capital intensity has no influence on tax aggressiveness. Independent commissioners are unable to moderate leverage and capital intensity on tax aggressiveness. Keywords: Awareness; Leverage, Capital Intensity, Aggressiveness, Independent Commissioner